Vsevolod Garshin’s Dialogue with History: Notes on Vasily Surikov’s "Boyarynya Morozova" - Żejmo, Bożena (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The author of the article analyzes a review by the Russian writer and critic Vsevolod Garshin for his perception of Vasily Surikov’s painting Boyarynya Morozova. In the eyes of Garshin Morozova, an apologist of the Old Rite, is an irrational fanatic, sacrificing her life for mere phantoms. Garshin judges Morozova’s martyrdom in a very emotional and subjective way and does not understand the cultural and historic meaning of the act. The personal nature of Garshin’s dialogue with history is emphasized in the article.